Addressing the gastrointestinal health associated with schizophrenia: The argument for a new nutrition-based intervention - Robst, John (Journal of Schizophrenia Disorders And Therapy, 2016)
The purpose of this paper is to review the literature linking schizophrenia with chronic inflammation and gluten sensitivity. In addition, the paper discusses the need for dietary interventions that may improve multiple health outcomes for patients. Individuals with schizophrenia are at much greater risk for the development of additional autoimmune disorders. Second generation anti-psychotic medications are the most effective treatment for schizophrenia, but there are numerous potential side effects to the medications. More specifically, individuals with schizophrenia who are treated with SGAs are at increased risk for obesity, diabetes, as well as elevated lipids and blood pressure. An effective evidence-based dietary intervention has the potential to improve numerous outcomes for individuals with schizophrenia.
Keywords: Schizophrenia; Gluten Sensitivity; Chronic Inflammation; Dietary Interventions; Autoimmune Disorders